Prediction of the vibro-acoustic response of a structure-liner-fluid system based on a patch transfer function approach and direct experimental subsystem characterisation. (November 2016) - Albert, Christopher G.; Veronesi, Giorgio; Nijman, Eugène; Rejlek, Jan
Abstract: The vibro-acoustic response of a structure-liner-fluid system is predicted by application of a patch transfer function (PTF) coupling scheme. In contrast to existing numerical approaches, PTF matrices of structure and liner are determined by a direct experimental approach, avoiding the requirement of material parameters. Emphasis is placed on poroelastic lining materials. The method accounts for surface input and next-neighbour transfer terms and for cross and cross-transfer terms through the specimen. Shear stresses and transfer terms to further patches on the liner are neglected. A single test-rig characterisation procedure for layered poroelastic media is proposed. The specimen is considered as a single component – no separation of layers is performed. For this reason the characterisation procedure can serve as a complement to existing methods if separation of layers is not possible and as a tool for validation of more detailed material models. Problem specific boundary conditions for skeleton and fluid, which may cause non-reciprocal cross terms, are dealt with by the procedure. Methods of measurement for the assessment of PTF matrices are presented and their accuracy and limitations are discussed. An air gap correction method for surface impedance measurements is presented.